Formação inicial e áreas de atuação profissional de egressos do curso de Licenciatura Plena em Ciências Biológicas da Universidade Federal de Mato Grosso do período de 2004 - 2009 - Uliana, Edna Regina (2011)
The finding that the shortage of teachers of secondary school is one of the shortcomings of Brazilian education motivated this study whose purpose is to analyze the initial training and professional performance of graduates of the course of Full Degree in Biological Sciences (from 2004 to 2009) Federal University of Mato Grosso, Cuiabá campus, seeking to establish relations between these two dimensions of the professionalization process. This is a case study approach with qualitative and quantitative. Data were obtained through analysis of documents (laws, decrees, resolutions, the education program, among others) of questionnaires and interviews with graduates. The analysis indicates that for a long time, promoted the formation in the course of Biological Sciences followed the model of teaching scheme called "3 +1". This designation is related to the fact that the first three years are for the study of specific knowledge and the latest study of the didactic and pedagogical issues. It is considered that this teaching model, coupled with technical rationality, a bonus has a degree of bachelor. The numerous and damning criticism of this model indicate the need for clear definition of the identity of the licensee. In this sense, it is pointed out as a way to adopt a 'new' model of education based on practical rationality. The proposed changes would shift the focus of the training of teaching content specific to the practice, which requires considering the teacher as a producer of knowledge. The speech that makes the defense of practical rationality is present in the literature, and explicitly in the National Curriculum Guidelines that, at present, direct the training of teachers of basic education. However, data from this study indicate that although the aforementioned guidelines have driven the distinction between bachelor's degree and the National Curriculum Guidelines for Biological Sciences courses were formulated with a view to serve both as a BA degree, characterized therefore as a hybrid text. This hybridization was observed in the pedagogical project of the degree course in Biological Sciences UFMT, since this was aimed both at biologists and training as teachers. Data from this study indicate, with respect to the areas of professional practice, graduates of the undergraduate course in question is operating in various fields such as biologists and / or as teachers. In the opinion of the study subjects was weakness in teacher training. However, the most relevant aspect of the course was aimed more training for the research made possible especially by the disciplines of ecology, but also through the stages of scientific initiation (PIBIC or VIC). In short, the set of data from this study to suggest that the majority of graduates found the training "hybrid" promoted by the course as good quality because it facilitates the work of two professional profiles. This fact gives evidence that the problem of teacher training is not restricted to the split between baccalaureate and graduate and consequent clear definition of the identity of both. There are reasons to believe that the shortage of teachers in the area of Natural Sciences is related particularly to the nonattractiveness of teaching, expressed in the casualization of teaching. We understand that this question can only be resolved by public policies that enhance the teaching profession by ensuring quality education, adequate working conditions and decent wages, basic requirements for the construction of professionalization.